Nevertheless, I have persisted - Melissa J. Freeman (Qualitative Research in Medicine & Healthcare)
In the early morning hours of one night, when I am a neurology resident on call at the hospital, I am paged to a stroke alert. This means I had to run to the emergency room to see, assess, and treat a critically ill patient. (...)